Психолого-педагогическая подготовка старшеклассников в процессе профессиональногосамоопределения - Дуйсембекова, Ш.Д. (My University, 2016)
This article informs us about the professional students self – defining in the field of self –oriented education the Carried the research makes an important contribution to reformation of secondary educational schools within the framework of 12-year education and higher form student’s professional self- determination in conditions of individually orientied education and represents one of the alternative approaches to solving of setting the problem
Keywords: professional self-determination; preparation; personality; senior pupil; profession; development